Between the royal administration and local elite: the pā‹ātu in Hellenistic Babylonia as epistates? - Boiy, Tom (Anabasis. Studia Classica et Orientalia, 2010)
The paper deals with the status of the cities in Hellenistic Babylonia and the nature of the offices called epistates and pā‹ātu. The exact authority and legal position of an epistates and a pā‹ātu is discussed.